The effect of retinol binding protein on the proteome of C2C12 muscle cells. Issue 4 (3rd December 2015) - Young, Pamela A.; Leonard, Siobhán; Martin, Darren S. D.; Findlay, John B. C.
Abstract: Background: Retinol binding protein (RBP) and its membrane receptor, STRA6, are vital for the management of vitamin A in the body. Recently, elevated serum RBP levels have been implicated as a contributing factor to the development of insulin resistance and type 2 diabetes. However, conflicting opinions exist as to how these increased levels can cause insulin resistance. Methods: In order to better understand the influences of RBP, a proteomic study was devised to determine the direct effect of RBP on a mouse muscle cell line, because the muscle is the principal site of insulin induced glucose uptake. C2C12 cells were treated with RBP for 16 h and the proteome analysed for alterations in protein abundance and phosphorylation by 2‐DE. Results: A number of changes were observed in response to retinol binding protein treatment, of which the most interesting were decreased levels of the phosphatase, protein phosphatase 1 β . This phosphatase is responsible for regulating glycogen synthase and glycogen phosphorylase, the rate‐limiting enzymes involved in glycogen storage and utilization. Retinol binding protein treatment resulted in increased phosphorylation and inhibition of glycogen synthase, with detrimental effects on insulin stimulated glycogen production in these cells. Conclusion: The results indicate that RBP may have a negative effect on energy storage in the cell and could contribute to the development of insulin resistance in muscle tissue. Understanding how retinol binding protein influences insulin resistance may reveal novel strategies to target this disease. Copyright © 2015 John Wiley & Sons, Ltd.